Low hydration status may be associated with insulin resistance and fat distribution: analysis of the Korea National Health and Nutrition Examination Survey (KNHANES) 2008–2010. Issue 2 (19th March 2020) - Min, Hyang K.; Ko, Hyun Y.; Kim, Jin T.; Bankir, Lise; Lee, Sung W.
Abstract: We aimed to identify the association of hydration status with insulin resistance (IR) and body fat distribution. A total of 14 344 adults participated in the Korea National Health and Nutrition Examination Survey 2008–2010. We used urine specific gravity (USG) to indicate hydration status, and HOMA-IR (homoeostasis model assessment of IR) and trunk:leg fat ratio (TLR) as primary outcomes. In multivariate logistic regression, the OR per 0·01 increase in USG for high IR was 1·303 (95 % CI 1·185, 1·433; P < 0·001). In multivariate generalised additive model plots, increased USG showed a J-shaped association with logarithmic HOMA-IR, with the lowest Akaike's information criterion score of USG 1·030. Moreover, increased USG was independently associated with increased trunk fat, decreased leg fat and increased TLR. In mediation analysis, the proportion of mediation effects of USG on TLR via IR was 0·193 (95 % CI 0·132, 0·285; P < 0·001), while the proportion of mediation effects of USG on IR via TLR was 0·130 (95 % CI 0·086, 0·188; P < 0·001). Increased USG, a sign of low hydration status and presumably high vasopressin, was associated with IR and poor fat distribution. Direct effect of low hydration status may be more dominant than indirect effect via IR or fat distribution. Further studies are necessary to confirm our findings.